STRATEGI PUBLIC RELATIONS PT KAI DALAM MEREDAKAN SENTIMEN NEGATIF PUBLIK TERKAIT ISU PELECEHAN SEKSUAL DI ATAS KRL - Emmy Suryani; Sa'diyah El Adawiyah (SOURCE : Jurnal Ilmu Komunikasi, 2023)
This study aims to identify the Public Relations strategy implemented by KAI Commuter Line in reducing negative sentiment regarding the issue of sexual harassment on trains. This research was conducted by following a qualitative descriptive research approach. The examined data were collected using literature study techniques. The data sources were obtained from books, journals, articles, news, and uploaded media on various social media. The data that has been collected is then analyzed and classified. In this stage, the image recovery theory proposed by Benoit is applied. Its application is carried out by classifying data into the five basic image recovery strategies initiated by Benoit. The five basic strategies include: denial, evading responsibility, reducing the offensiveness of events, and corrective action. After this classification is carried out, the next step is to determine what strategies are implemented by Public Relations in dealing with negative sentiments regarding sexual harassment on the train. The findings of this study prove that PR has implemented the four image recovery strategies proposed by Benoit. These strategies are strategies for mortification, denial, corrective action, and strategies for reducing the offensiveness of events. The implementation of these four strategies can overcome negative public sentiment and restore PT KAI's image.